High-performance photocatalytic reduction of Cr(VI) using a retrievable Fe-doped WO3/SiO2 heterostructure - Natkritta Boonprakob; Duangdao Channei; Chen Zhao (Discover Nano, 2024)
Abstract The enhancement of the photocatalytic performance of pristine WO3 was systematically adjusted due to its fast recombination rate and low reduction potential. A designed heterostructure photocatalyst was necessarily synthesised by Fe3+ metal ions doping into WO3 structure with and composition modification. In this study, we synthesised a retrievable Fe-doped WO3/SiO2 heterostructure using a surfactant-assisted hydrothermal method. This heterostructure was then employed as an effective photocatalyst for the removal of Cr(VI) under visible light irradiation. Enlarged photocatalytic reduction was observed over a synergetic 7.5 mol% Fe-doped WO3/SiO2-20 nanocomposite, resulting in dramatically increased activity compared with undoped WO3 and SiO2 nanomaterials under visible light illumination within 90 min. The presence of 7.5 mol% Fe3+ ion dopant in WO3 optimised electron–hole recombination, consequently reducing WO3 photocorrosion. After adding SiO2 nanoparticles, the binary WO3-SiO2 nanocomposite played roles as both adsorbent and photocatalyst to increase specific surface area. Thus, the 7.5 mol% Fe-doped WO3/SiO2-20 nanocomposite catalyst had more active sites on the surface of catalyst, and enhanced photocatalytic reduction was significantly achieved. The results showed 91.1% photocatalytic reduction over the optimum photocatalyst, with a photoreduction kinetic rate of 21.1 × 10–3 min−1, which was approximately four times faster than pristine WO3. Therefore, the superior optimal photocatalyst demonstrated reusability, with activities decreasing by only 9.8% after five cycles. The high photocatalytic performance and excellent stability of our photocatalyst indicate great potential for water pollution treatments.